2017
DOI: 10.1159/000468931
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll-Like Receptor-Myeloid Differentiation Factor 88 Expression at the Maternal-Fetal Interface Is Associated with Spontaneous Abortion

Abstract: Aims: Toll-like receptors (TLRs) form a group of pattern recognition receptors that play a major role in maintaining innate host immunity. Myeloid differentiation factor 88 (MyD88) is an adaptor molecule that is essential for signaling via the TLR family. To analyze the mechanism of the imbalance in the innate immune system mediated by TLRs-MyD88 in spontaneous abortion, we detected the expression of TLR-2, TLR-4, TLR-7, and MyD88 in placentae and deciduas. Methods: The expression of TLR-2, TLR-4, TLR-7, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…In this study, anti-β2-GP1 antibodies and ACAs were induced by injecting mice with β2-GP1 to construct the autoimmune RSA mouse model ( 17 ). Based on the current understanding of that disease model, aspirin, VitD3, and progesterone were used to intervene in the pregnancy outcome of autoimmune RSA.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, anti-β2-GP1 antibodies and ACAs were induced by injecting mice with β2-GP1 to construct the autoimmune RSA mouse model ( 17 ). Based on the current understanding of that disease model, aspirin, VitD3, and progesterone were used to intervene in the pregnancy outcome of autoimmune RSA.…”
Section: Introductionmentioning
confidence: 99%
“…129 Specifically, it may shift the immune responses to the Th1 inflammatory responses and induce the death of trophoblast, which can result in miscarriage. 130 Furthermore, Inflammatory activation of endometrial immune cells by viruses can cause an excessive maternal immune response toward the trophoblastic invasion and induce miscarriage. 131 IL-1, IL-6, and tumor necrosis factor TNF-α are involved in the local inflammatory process and attract neutrophils to the site of infection.…”
Section: Alteration Of Trophoblast Invasion and Placental Dysfunctionmentioning
confidence: 99%
“…Recent studies have suggested that the placenta functions as an active immunologic barrier by trophoblasts recognizing and responding to microbes through innate immune pattern recognition receptors (PRRs) (6)(7)(8)(9). PRRs are essential for innate immune system responses to infectious microorganisms and recognize conserved sequences known as pathogen-associated molecular patterns (PAMPs).…”
Section: Introductionmentioning
confidence: 99%